Communication Patterns of Teachers and Parents in Online Learning for the Academic Development of Kindergarten Students: Pola Komunikasi Guru Dan Walisantri Pada Belajar Online Untuk Perkembangan Akademik Siswa TK - Eva Yohana; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2021)
The study aims to know the patterns of teacher communication and keep up on studying online for the academic development of kindergartners. Khoiru ummah located on a residential garden complex block B2 no.11, fragrant village sukodono district district sidoarjo. The method used for the reception analysis, the theory used was public communication and mass, a refined model of laswell barddock (1958).Then analyzed the wheel communication patterns for the students' academic development results. The data-mining techniques used are observations, interviews, online documentation studies. The results of this research show. The communication patterns of teachers and quehies have not developed for students as they lack sufficient insights into the technology and lack of openness of parental participation in working and collecting online tasks from the school, this is seen when students do not complete the learning test assignments firsthand